Validation of chromatography data systems - McDowall, Robert (RSC chromatography monographs., 2017)
Guiding chromatographers working in regulated industries and helping to validate their chromatography data systems, this book will be a detailed look at the requirements to ensure a system is fit for purpose throughout the life cycle.